Hidden in plain sight: Gender analysis of the environmental and social impact assessment of the East African crude oil pipeline - Hill, Christina; Namara, Charité; Orcaya, Jane; Bogrand, André; Sellwood, Scott A. (Impact Assessment and Project Appraisal, 2021)
Large-scale mining, oil, and gas projects can have a profound and negative affect on women’s rights and gender equality. Adverse impacts include the disruption of family and social life; the increased risks to health and safety, especially in terms of domestic and sexual violence; environmental degradation; as well as changing access to and control over land and livelihoods. These adverse impacts fall most heavily on women. This case study focused on the East African Crude Oil Pipeline (EACOP). It shows that conventional environmental and social impact assessment (ESIA) processes may not identify all potential adverse impacts on women, and can fail to analyse the implications of potential impacts on gender norms and gender power relations, leading to a downplaying of the significance of these impacts. The implications for women and girls’ health and safety resulting from the in-migration of large numbers of mostly men seeking project employment and other opportunities and increases in women’s unpaid care work are two potential adverse impacts the EACOP ESIA failed to identify. Strengthening gender analysis within the current suite of impact assessment tools and methodologies, particularly for extractive industries projects, is therefore urgently needed. © 2021 IAIA.
Keywords: 2000 à aujourd'hui; afrique; approches et analyses; environnement; extractivisme; industrie pétrolière; ouganda; patriarcat; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; santé des femmes*; systèmes d'oppressions; thématiques; violences